A health care professionals training needs assessment for oncology in Uganda - Josaphat Byamugisha; Ian G. Munabi; Aloysius G. Mubuuke; Amos D. Mwaka; Mike Kagawa; Isaac Okullo; Nixon Niyonzima; Pastan Lusiba; Peruth Ainembabazi; Caroline Kankunda; Dennis D. Muhumuza; Jackson Orem; et al. (BMC, 2020)
Abstract Background Cancer incidence and mortality in sub-Saharan Africa are increasing and do account for significant premature death. The expertise of health care providers is critical to downstaging cancer at diagnosis and improving survival in low- and middle-income countries. We set out to determine the training needs of health care providers for a comprehensive oncology services package in selected hospitals in Uganda, in order to inform capacity development intervention to improve cancer outcomes in the East African region. Methods This was a cross-sectional survey using the WHO Hennessey-Hicks questionnaire to identify the training needs of health workers involved in cancer care, across 22 hospitals in Uganda. Data were captured in real time using the Open Data Kit platform from which the data was exported to Stata version 15 for analysis using the Wilcoxon signed-rank test and Somers-Delta. Results There were 199 respondent health professionals who were predominately female (146/199, 73.37%), with an average age of 38.97 years. There were 158/199 (79.40%) nurses, 24/199 (12.06%) medical doctors and 17/199 (8.54%) allied health professionals. Overall, the research and audit domain had the highest ranking for all the health workers (Somers-D = 0.60). The respondent's level of education had a significant effect on the observed ranking (P value = 0.03). Most of the continuing medical education (CME) topics suggested by the participants were in the clinical task-related category. Conclusion The "research and audit" domain was identified as the priority area for training interventions to improve oncology services in Uganda. There are opportunities for addressing the identified training needs with an expanded cancer CME programme content, peer support networks and tailored training for the individual health care provider.